Assessment of 2, 4- D residues in the major rice soils of Kerala - Durga Devi K M (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 2002)
An attempt was made to assess the behaviour of 2,4-D in the three major rice soils of Kerala viz., Palakkad, kuttanad and kole lands. Three laboratory experiments were conducted in sixteen soil samples (five each from Palakkad and kuttanad and six from kole lands) collected from the major rice growing regions, so as to understand the persistence, degradation, adsorption and leaching pattern of 2,4-D in these samples. A field experiment was also conducted in kole area of Thrissur district (farmer's field at pidikkaparambu) for estimating the dissipation pattern of 2,4-D from soil and plant uncier field condition. In order to estimate 2,4-D residues in soil samples of the laboratory experiments, a colorimetric procedure was standardized. . The standardization process consisted of selection of estimation procedure, standardization of extractants and soil extractant ratios and clean up method. Among the different extractants tried, acetonitrile: distilled water: glacial acetic acid (80:20:2.5) in the soil extractant ratio of I:4 was the best on in terms of recovery of applied 2,4-D from soil. Clean up of the exctract with chemicals in sequence: NaOH (IN), concentrated HCl, diethyl ether, sodium hydrogen phosphate buffer, concentrated HCl and carbon tetrachloride was efficient to remove the co-extractives. Heating the residue with chromotropic acid in concentrated sulphuric acid at 135 QC for 20 min. was employed to develop the colour. Absorbance of the coloured extract was measured